2020
DOI: 10.7567/1347-4065/ab5bc0
|View full text |Cite
|
Sign up to set email alerts
|

Study of oxygen and ozone reactions on surfaces previously treated by ozone

Abstract: The inner surfaces of three samples (alumina and copper tubes, ozonizer) were treated by ozone. The surface reactions of oxygen and ozone were studied after this treatment. The surface reaction of gaseous molecular oxygen leads to fast ozone creation. The created ozone again reacts with the surface, which leads to its destruction. These reactions can be explained as surface reactions between adsorbed oxygen atoms and molecules or as surface reactions of these adsorbed species with gaseous species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Marinov et al [27,38] and Lopaev et al [26] proposed models with ozone production proportional to the incident O atom flux. Lopaev et al [26] also proposed surface production of O 3 on fused silica by the recombination of O 2 with quasi-physisorbed O atoms, and Mazánková et al proposed a similar mechanism on alumina and copper surfaces [26,39]. We compared the results of different surface ozone production models with the present experimental results: (1) proportional to O atom flux and (2) proportional to the O 2 flux.…”
Section: Ozone Surface Productionmentioning
confidence: 62%
See 1 more Smart Citation
“…Marinov et al [27,38] and Lopaev et al [26] proposed models with ozone production proportional to the incident O atom flux. Lopaev et al [26] also proposed surface production of O 3 on fused silica by the recombination of O 2 with quasi-physisorbed O atoms, and Mazánková et al proposed a similar mechanism on alumina and copper surfaces [26,39]. We compared the results of different surface ozone production models with the present experimental results: (1) proportional to O atom flux and (2) proportional to the O 2 flux.…”
Section: Ozone Surface Productionmentioning
confidence: 62%
“…The possibility of such a cyclic mechanism of ozone surface destruction is discussed by Mazankova et al [39] for alumina and copper surfaces previously treated by ozone. Mankelevich et al [7] studied ozone loss on Al 2 O 3 surfaces, and suggested a mechanism consisting of the formation of a layer of chemisorbed O 3 (attached to surface Al atoms) followed by O 3 phyisorption (O 3phys ) and further reactions of O 3phys with incident ozone molecules.…”
Section: Surface Destruction Of Ozonementioning
confidence: 99%
“…(The subscript s denotes a surface species.) These reactions for O 3 destruction have been proposed by several researchers [6,13,25]. As will be discussed in section 4, W s is more abundant than O s and is therefore responsible for the majority of O 3 destruction on the surface.…”
Section: Description Of the Modelmentioning
confidence: 84%
“…Yanallah et al simulated O 3 production and showed that including O 3 loss reactions on the surfaces changed the electrical characteristics of the discharge [5]. Mazánková et al exposed copper and aluminum surfaces to O 3 produced by an ozonizer to study surface composition [6]. They showed that the elemental O composition of those surfaces increased after exposure to O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…(For example, the rate coefficient for the reaction of N 2 O 5 with O atom is less than 3 × 10 −22 m 3 s −1 [74].) Furthermore, the model does not include surface reactions, which can contribute to atomic species recombination [75], ozone creation and destruction [76][77][78] and NO oxidation to NO 2 [79].…”
Section: Chemical Kinetic Modelmentioning
confidence: 99%